PENGARUH PROFITABILITAS, STRUKTUR AKTIVA DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PT.TIMAH TBK PERIODE 2013-2019 - Salsyabilla, Nyimas Dinda; Wuryanti, Lestari; Rahyono, Rahyono (Universitas Malahayati, 2022)
This study aims to determine the effect of profitability, asset structure and sales growth on the capital structure of PT.Timah Tbk for the 2013-2019 period. The data analysis technique in this study is quantitative analysis which is expressed by numbers and the calculations use statistical methods assisted by the SPSS 25.0 program. The results of this study with multiple linear regression test showed that partially the Profitability variable has a negative and significant effect on capital structure, Asset Structure partially has no effect on capital structure, Sales Growth partially has no effect on capital structure. The results of the regression test calculation together (Ftest) show that the variables Profitability (X1), Asset Structure (X2) and Sales Growth (X3) together have a positive and significant effect on the Capital Structure of PT.Timah Tbk.